2019
DOI: 10.1002/chem.201806430
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Steric and Electronic Effects: A Joint Spectroscopy and Computational Study of Nonheme Iron(IV)‐Oxo Complexes

Abstract: Iron is an essential elementi nn onheme enzymes that plays ac rucial role in many vital oxidative transformations and metabolic reactions in the human body.M any of those reactions are regio-ands tereospecific and it is believed that the selectivity is guided by second-coordination sphere effects in the protein. Here, results are shown of a few engineered biomimetic ligand frameworks based on the N4Py (N,N-bis(2-pyridylmethyl)-N-bis(2-pyridyl)methylamine) scaffold and the second-coordination sphere effects are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 95 publications
4
67
0
Order By: Relevance
“…[64][65][66][67][68][69][70][89][90][91][92][93] By contrast, with iron in octahedral coordination environment typically a triplet spin ground state is found with the quintet spin well higher in energy. [94][95][96][97] The optimized geometry of the reactant structures also highlights key interactions of the substrate with the protein that lock it into position. Thus, the phenol group of the substrate forms hydrogen bonding interactions with the alcohol groups of Ser 236 and Thr 239 .…”
Section: Methodsmentioning
confidence: 99%
“…[64][65][66][67][68][69][70][89][90][91][92][93] By contrast, with iron in octahedral coordination environment typically a triplet spin ground state is found with the quintet spin well higher in energy. [94][95][96][97] The optimized geometry of the reactant structures also highlights key interactions of the substrate with the protein that lock it into position. Thus, the phenol group of the substrate forms hydrogen bonding interactions with the alcohol groups of Ser 236 and Thr 239 .…”
Section: Methodsmentioning
confidence: 99%
“…All calculations were done for the doublet and quartet spin states. These methods have previously been applied for the studies of enzymatic reaction mechanisms and shown to reproduce experimental rate constants, regioselectivities and kinetic isotope effects well [96][97][98][99][100][101].…”
Section: Qm/mm Calculationsmentioning
confidence: 99%
“…Although the quinoline entity is a relatively strong donor, the weakened equatorial field that is a consequence of the steric effect results in higher HAT and OAT rates relative to other iron complexes containing ligands of the N4Py framework. 27 Considering the established high reactivity of 7 and the steric nature of its origin, and the ability of its precursor 3 to function as a ( pre)catalyst for alkane and alkene oxidation, we…”
Section: Generation and Characterization Of [Fementioning
confidence: 99%